Mining SNP loci and candidate genes for sheath blight resistance in Indica rice using genome-wide association studies - Gu, Xin; Ding, Junjie; Xu, Hui; Liu, Wei; Wu, Hui; Tang, Qiang; Yang, Shuai; Wang, Ling; Zhang, Suhua; Chen, Long; Meng, Xue; Tao, Ye; et al. (Frontiers in Plant Science, 2025)
Rice is a vital component of the global food supply chain. Sheath blight (ShB) poses a severe threat to indica rice production, resulting in substantial yield and quality deteriorations. Although chemical control strategies are widely employed, their prolonged use raises concerns about the development of pathogenic resistance. Genome-wide association studies (GWAS) serve as a critical tool for identifying genetic loci associated with ShB resistance. However, current research efforts are constrained by limitations in sample size, environmental influences, and analytical methodologies. Notably, studies on ShB resistance have focused mainly on japonica rice, with indica rice receiving limited attention in GWAS-based investigations. Prioritizing GWAS research targeting ShB resistance in indica rice is essential for enriching disease resistance gene resources and facilitating molecular breeding programs. Eighty-four indica accessions were subjected to in vitro phenotyping for ShB resistance, followed by whole-genome resequencing using a magnetic bead-based DNA extraction protocol. Population structure analysis revealed high genetic diversity (K = 5) with normally distributed resistance phenotypes. From 2.93 million raw SNPs, 904,708 high-quality variants were retained for multi-model GWAS (GLM/MLM/EMMAX/GEMMA), identifying 22 consensus loci. Haplotype blocks delineated three critical regions harboring 15 candidate genes, including ABC transporters and calmodulin-like proteins with putative roles in pathogen defense, among others. Functional annotation revealed that ABCG transporters, calmodulin-like proteins (CMLs), non-specific lipid transfer proteins (nsLTPs), and receptor-like serine/threonine kinases orchestrate defense responses through calcium-mediated signaling, antimicrobial metabolite translocation, and maintenance of membrane integrity. qPCR analysis revealed that the three GWAS-associated candidate genes were significantly upregulated after R. solani inoculation in the resistant line X-11, suggesting that variations in their non-coding regions contribute to disease resistance by enhancing both basal and pathogen-induced expression. These loci constitute a genetic toolkit for deciphering Rhizoctonia solani Kühn (R. solani) resistance mechanisms and facilitate precision breeding in indica rice.